(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The simulation models of variable-frequency electric drives with direct torque control were built in MATLAB / Simulink simulation environment. These models are shown and described in the article. А number of energetic characteristics of the electric drives being investigated are considered. The calculations of these characteristics were made on the computer models and the comparative analysis of the values obtained is given.